2006
DOI: 10.1038/sj.cdd.4402076
|View full text |Cite
|
Sign up to set email alerts
|

A novel cell type-specific role of p38α in the control of autophagy and cell death in colorectal cancer cells

Abstract: Cancer develops when molecular pathways that control the fine balance between proliferation, differentiation, autophagy and cell death undergo genetic deregulation. The prospects for further substantial advances in the management of colorectal cancer reside in a systematic genetic and functional dissection of these pathways in tumor cells. In an effort to evaluate the impact of p38 signaling on colorectal cancer cell fate, we treated HT29, Caco2, Hct116, LS174T and SW480 cell lines with the inhibitor SB202190 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 38 publications
(48 reference statements)
6
140
1
Order By: Relevance
“…Inhibition of p38MAPK increases autophagy triggered by 5-FU It has been recently reported that modulation of autophagy can affect the cellular resistance to 5-FU (Li et al, 2009, and inhibition of p38MAPK can modify autophagy in several cell types, including colorectal cancer cells (Comes et al, 2007). Therefore, we analyzed the effect of p38MAPK inhibition in the autophagic response to 5-FU.…”
Section: P38mapk Is Activated In Response To 5-fu/5-dfur and Mediatesmentioning
confidence: 99%
“…Inhibition of p38MAPK increases autophagy triggered by 5-FU It has been recently reported that modulation of autophagy can affect the cellular resistance to 5-FU (Li et al, 2009, and inhibition of p38MAPK can modify autophagy in several cell types, including colorectal cancer cells (Comes et al, 2007). Therefore, we analyzed the effect of p38MAPK inhibition in the autophagic response to 5-FU.…”
Section: P38mapk Is Activated In Response To 5-fu/5-dfur and Mediatesmentioning
confidence: 99%
“…On one hand, p38 promotes autophagy in response to glucose (42,43). On the other hand, pharmacological inhibition of p38 activity with SB202190 or genetic knockdown with p38 siRNA induces autophagy in colorectal cancer cells (30). The basis for these differences is not clear, but may in part be cell context-dependent or influenced by the type of autophagic stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the function of TOPK in solar UV lightinduced skin carcinogenesis might be decided primarily by the role of its downstream p38␣ in tumor development. Several studies have described decreased activity of the p38 pathway in different human cancers (33)(34)(35). Genetic modification of different members of this pathway revealed that p38␣ can function as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%